Crystal structure modulation of SnSe thermoelectric material by AgBiSe2 solid solution. Issue 8 (July 2023) - Wang, Hongxiang; Tan, Chang; Romanenko, Anatoly; Sun, Yuqing; Feng, Juanjuan; Khan, Mahwish; Chebanova, Galina; Wang, Long; Yao, Jie; Wang, Hongchao; Wang, Chunlei
Abstract: Although low thermal conductivity and high band degeneracy bring promising thermoelectric performance to cubic SnSe, its preparation strategies remain elusive. Here, a series of Sn1–2 x (AgBi) x Se samples are synthesized using the vacuum melting (1173 K) and spark plasma sintering (723 K) methods. Owing to the increased configurational entropy caused by AgBiSe2 solid solution, the cubic structure is obtained when x exceeds 0.2. The optimized carrier concentration significantly enhances electrical conductivity ( σ ), and maximal σ of 350 Scm −1 is obtained in Sn0.5 (AgBi)0.25 Se. Combined with the low lattice thermal conductivity caused by the small sound velocity and strong anharmonicity, the figure of merit of 0.08 is reached in Sn0.6 (AgBi)0.2 Se at 500 K. The mechanical performances are also improved, and a high Vicker hardness of 1.5 GPa is obtained in Sn0.4 (AgBi)0.3 Se. This work demonstrates the importance of the configurational entropy in phase regulation and provides insights into the design of new thermoelectrics.